VISUALISASI POTENSIAL LISTRIK DI ANTARA DUA PLAT SEJAJAR BERHINGGA DENGAN PROGRAM KOMPUTER BERBASIS MATLAB - Eviliony Eviliony; Erwin Erwin; Antonius Surbakti (Komunikasi Fisika Indonesia, 2018)
The calculation of electric potential between two parallel plates with finite size is difficult work, visualization of the issue comprehensively is needed. In this paper, visualization of electric potential between two parallel plates with finite size has been done by developing a MATLAB based computer program. The electric potential was calculated by solving two dimensional Laplace equation. There are two parts of the program that have been developed, the menu program and the main program. The menu program was provided to store the input data required in the calculation. While, the main program served toperform calculations and visualization of the electric potential. The visualization of the electric potential was shown in the mesh and contour graph. The results showed that the program is applicable for various sizes of plates, and the electric potential in each position can be calculated and visualized. However, the computer programs has some limitations, such as for perfoming calculations of electric potential. For plate width ( ) of  m, distance of plates ( ) of  m, and initial potential ( )of  Volt, the electric potential in coordinate (20,0.5) is not defined (NaN).